Estimation of transboundary air pollution on the basis of synoptic-scale weather types - Helmis, C.G.a; Moussiopoulos, N.b; Flocas, H.A.a; Sahm, P.b; Assimakopoulos, V.D.a; Naneris, C.b; Maheras, P.c (International Journal of Climatology, 2003)
A methodology to estimate annual transboundary atmospheric transport is proposed, taking into account different background meteorological conditions. For this purpose, the 850 hPa synoptic-scale atmospheric circulation over the area examined was classified on a daily basis into 14 distinct synoptic types, using a database for an extended period of 40 years. The corresponding frequency of appearance of the synoptic types for a normal year was calculated. For selected days representing the synoptic types during this year, the inflow-outflow fluxes of NOx and SO2 were estimated through a balancing box with the aid of a MEMO/TRAPPA modelling system. According to the proposed method, the total inflow-outflow fluxes were calculated using the lateral fluxes for each representative day, being weighted by the annual relative frequency of appearance of the synoptic scale weather types. It was demonstrated that this approach provides similar results to the intensive method based on day-by-day calculations. Furthermore, this approach is easier to use, since it is based on the simulations of selected days, and it allows the investigation of the influence of different types of atmospheric circulation on the inflow-outflow budget. Copyright © 2003 Royal Meteorological Society.
Keywords: Air pollution; atmospheric circulation; Climatology; computer simulation; Database systems; nitrous oxide; Sulfur dioxide; Synoptic meteorology; Transboundary air pollution; transboundary pollution; weather forecasting